Analisis Kegagalan Konstruksi Dan Bangunan Dari Perspektif Faktor Teknis - Yustinus Eka Wiyana (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2012)
Failure of construction and building may be caused by technical factors. Technical factors due to lower bid price (less than 70 per cent of the price standard, so that contractors tend to carry out the project does not match the technical specifications / contract, do not prepare the necessary documents for project control and low labor resource capabilities. This paper was to analyze the failures and failure Building Construction from the Perspective of technical factors, the 34 building projects in Central Java. The results of this study indicate that for building projects, construction and building failure occurred in many elements of the structure with an average deviation of 4.36% of the contract value, followed by the roof (2.53%), foundations (0.15% ), utilities (0.12%) and finishing (0.07%).